Diffractive shadowing of coherent polarization radiation; Physics Letters A; Vol. 391 - Curcio A. Alessandro; Bergamaschi M.; Corsini R. Roberto; Gamba D. Davide; Farabolini W. Wilfrid; Kieffer R.; Lefevre Th. Thibaut; Potylitsyn A. P. Alexander Petrovich (2021, 2021)
Title screen